Modeling and simulation of everyday things - Roth, Michael W., PhD (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
'The content of this book comes directly from my research with students as well as my having taught Modeling and Simulation of Physical Systems in a Professional Science Masters' class. So it's got proof of concept from'here to the end of the block' and I want you to take heart in that if the going gets a bit rough. The book is designed for (i) persons who don't necessarily have experience in computer coding or physics, (ii) nonphysics and nonscience majors in community colleges, colleges and universities, (iii) students in Professional Science Masters' or other nonphysics graduate programs, and (iv) high school students in science courses. It's meant to support, encourage, and empower the reader to do some decent simulations of routine things with smatterings of what's beyond in order to challenge you to grow and expand'--
Building your basic toolbox -- Getting to know the neighborhood -- Visualizing your work and representing your best story -- In the news: the fun and the dangerous -- The dances of guitars, bridges, and atoms -- Going with the flow -- One of the most versatile simulation tools around -- Simulations that explore atoms and planets -- Parallel computing, scripting, and GPUs.
Includes bibliographical references.
Keywords: Computer simulation; Mathematical models